2019
DOI: 10.1094/pdis-08-18-1445-re
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genome Characterization of Field Isolates of Sugarcane Mosaic Virus (SCMV) in Nigeria

Abstract: Maize and sugarcane are two economically important crops often grown in adjacent fields or co-cultivated in the northern guinea savannah agroecological zone, a major cereal production region of Nigeria. This study was conducted to determine the prevalence of mosaic disease in sugarcane and maize fields in the northern guinea savannah agroecological zone and to molecularly characterize the associated sugarcane mosaic virus (SCMV, genus Potyvirus) isolates. Surveys were conducted from June to July 2015, and suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…W.D. Clayton) were recently reported infected by the same genetic populations of the virus in Nigeria, suggesting that interspecies transmission in this country was caused by aphid vectors probing or feeding on all three plant species (Yahaya et al 2019). A similar situation was reported in Iran, where sugarcane, maize, sorghum, and johnsongrass were infected by genetically closely related isolates of SCMV (Moradi et al 2017).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…W.D. Clayton) were recently reported infected by the same genetic populations of the virus in Nigeria, suggesting that interspecies transmission in this country was caused by aphid vectors probing or feeding on all three plant species (Yahaya et al 2019). A similar situation was reported in Iran, where sugarcane, maize, sorghum, and johnsongrass were infected by genetically closely related isolates of SCMV (Moradi et al 2017).…”
Section: Discussionmentioning
confidence: 61%
“…Historically, the CP has often been used for diagnosis of SCMV and characterization of its genetic diversity (Alegria et al 2003;de Souza et al 2012;G omez et al 2009;Handley et al 1998;Marie-Jeanne et al 2000;Moradi et al 2017;Yang and Mirkov 1997). More recently, full genome sequencing has been used to investigate variation within the virus and especially to analyze genomic evolution (Braidwood et al 2019;He et al 2020;Wamaitha et al 2018;Yahaya et al 2019). These studies revealed that SCMV is highly variable, with several recombination hotspots along its genome.…”
mentioning
confidence: 99%
“…The host adaptation of some potyviruses may be due to P1 protein, the most divergent ones in terms of length and aa sequence among the 11 mature proteins (Valli et al 2007;Salvador et al 2008;Maliogka et al 2012). P1 self-cleavage activity is indispensable for both potyviral viability and host range specificity (Valli et al 2007;Maliogka et al 2012;Pasin et al 2014;Shan et al 2015;Yahaya et al 2019). Sequence comparison shows that the P1 aa sequence of PalMV shares less than 30% identities with those of other potyviruses.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that credible and effective diagnosis of plant viruses is very crucial for generating disease management strategy. Meanwhile, this molecular test should be useful in supervising viral distribution and epidemiology (Marais et al 2015;Rajbanshi and Ali 2019;Yahaya et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A procedure has been developed to assess the presence of potyviruses in samples of infected cereals, followed by identification of the virus species or mix of species (in case of co-infection) of the genus Potyvirus [4]. MDMV and SCMV have been identified in maize plants on all continents [5][6][7][8][9][10][11][12][13][14][15][16], JGMV was found in Johnsongrass (Sorghum halepense), elephant grass (Pennisetum purpureum) and maize in Australia, USA, Brazil and Africa [17,18], and SrMV was identified in maize only in the USA and on sugar cane in China and India [1,3,19,20]. MDMV is the most common pathogen аmong all the viruses that infect maize worldwide [21].…”
mentioning
confidence: 99%